The implementation of a calibration plan of instruments in a metrological laboratory (Brazilian Journal of Radiation Sciences, 2021)
It is noticeable the importance of calibrating measuring instruments, as this process seeks to ensure metrological reliability. Therefore, it becomes possible to verify if the instruments present consistent results. This way, the metrological laboratory needs to keep its equipment calibrated, aiming to offer a satisfactory service to its customers. As the periodicity of instrument calibration is variable, i.e., they have different periods, due to the fact that this time depends on the usage frequency of the equipment, its manufacturing nature, the quality of its material, the environment in which it is being submitted, among other factors. This period variability leads to problems in the quality of the provided services, increase the costs in the logistics sector, in addition to causing managerial difficulties. For this reason, a calibration plan was presented, based on historical data of standard unavailability, aiming to estimate fixed calibration periods and, consequently, mitigate the observed problems.
Keywords: metrological reliability; calibration plan; standard unavailability.